(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Article devoted to the comparative legal analysis of the legal consequences arising from non-compliance with the terms of the contract in the countries of the Romano-German and Anglo-Saxon legal system.